Coupled Coincidence Point Theorems for a (β,g)-ψ-Contractive Mapping in Partially Ordered G-Metric Spaces: P. Charoensawan, C. Thangthong - Team, Support (Thai Journal of Mathematics, 2015)
In this paper, we introduce the notion (β)-admissible and (β, g)-admissible for mapping F : X × X → X and g:X→ X. We showed the existence of a coupled coincidence point theorem for a (β,g)-ψ-contractive mapping in G-metric spaces. We also show the uniqueness of a coupled common fixed point for such mappings and give some examples to show the validity of our result.